A large temperature-controlled static and dynamic mechanical testing apparatus on marine soil-structure interfaces for marine engineering - Yang, Bowen; Xu, Kaiwei; Tan, Kun; Cui, Peng; Feng, Xianhui (Frontiers in Marine Science, 2025)
Marine soil–structure interfaces are commonly encountered in marine engineering, where they are inevitably subjected to temperature variations and complex stress conditions, including static, dynamic, and creep loads. However, limited studies have addressed the temperature-dependent mechanical behavior of marine soil–structure interfaces under various loading scenarios. This study introduces a self-developed multifunctional large-scale shear apparatus that enables temperature-controlled testing of marine soil interfaces with various structural materials, including concrete, polymer grids, and polymer layers. The apparatus supports static, dynamic, and creep shear testing under precisely controlled thermal conditions. A series of shear tests were conducted on marine soil–concrete, marine soil–polymer grid, and marine soil–polymer layer interfaces to verify the device’s performance. The test results demonstrate that the apparatus can accurately and reliably capture the mechanical responses of marine soil–structure interfaces under different temperatures and loading modes. Furthermore, the results highlight the significant influence of temperature on the shear behavior of these interfaces, emphasizing the necessity of developing such equipment. The findings offer essential insights for the design, evaluation, and long-term stability of marine engineering structures, supporting the development of practical ocean solutions.